Programa educativo basado en el enfoque humanista y en la inteligencia emocional para mejorar las actitudes de los niños y niñas del sexto grado de educación primaria de la I.E. 88358, Pampas - Pallasca, 2012 - Mendoza Silva, Fanny Rosmery (2019)
ABSTRACT The purpose of the present investigation was demostred that application of a Educational Program based on the humanistic approach and Emotional Intelligence significantly influences in the improvement of children´s attitudes on sixth grade of primary education at the N° 88358 schools, Pampas-Pallasca, 2012. It used a population consisting of 186 students enrolled first to sixth grade of primary educational, and a sample of 26 students of sixth grade; it used quasi experimental research design with pretest and posttest to a single group. The collect data were worked through processing statistics techniques in order with hypothesis and the objectives testing our showed that the Educational Program was significantly influences in the improvement of children´s attitudes on sixth grade of primary education at the N° 88358 schools, Pampas-Pallasca; for that in conclusion the hypothesis was certificated with T of Student